PENGEMBANGAN PERANGKAT PENILAIAN BERBASIS KELAS UNTUK PEMBELAJARAN KIMIA SEKOLAH MENENGAH ATAS POKOK BAHASAN STOIKIOMETRI - Betty Holiwarni; Erviyenni ' (Jurnal Pendidikan Kimia Universitas Riau, 2016)
One of the causes that classroom-based assessment has not been applied in Senior High School nowadays because most of chemistry teachers have difficulties to develop the desired assessment as needed at the educational unit level curriculum. To solve this problem, a research was done to develop classroom-based assessment tool that is valid, practical, and effective for chemistry learning material in stoichiometry on Senior High School. The research method used was a development research. Research activities were conducted three years consisting of three stages, namely front-back analysis,prototyping, and implementation. Date were collected throught classroom observations, interviews with students, teachers, chemistry education expert,student work analysis, and achievement test. The result of first year showed that classroom-based assessment tool developed showed the validity criteria in term of its content and construction. The implementation conducted in the second year in SMAN 1 Pekanbaru, SMA Babussalam, and SMAN 2 Siak Hulu. The implementation result also showed the practical criteria, meaning that students and teachers can use it without significant constaint.